High Performance Management (HPM) in Sports in the International and Hungarian Literature - Gyerman, Istvan; Laczkó, Tamás (Stadium - Hungarian Journal of Sport Sciences, 2025)
High Performance Management (HPM) in sport is an integrated set of tools and approaches that aim to optimize the performance of athletes, sports organizations and sports disciplines at a multidimensional level (macro, meso, micro). The works of international literature – for example, Sotiridau - De Bosscher (2013), O’Boyle (2015), Molan et al. (2019) and Turner et al. (2019) – offer readers and researchers holistic models that integrate economic, psychological and human development factors into the HPM system. In contrast, the Hungarian literature (András, 2014; Géczi, 2012; Győri 2020) focuses primarily on economic, legal and organizational frameworks, highlighting the decisive role of domestic sports financing and institutional structures. The comparison of the two trends and the evaluation of the literature clearly highlights the fact that in Hungary the HPM system is fragmented and in most cases implemented in an ad hoc manner, while at the international level comprehensive, people-oriented and metrics-based models dominate. According to the conclusion of my research, the development of HPM in Hungarian sport requires the adaptation and acceptance of holistic approaches, the provision of sufficient personnel, the unification of performance indicators and the integration of the long-term well-being of athletes into the management processes of sports organizations and associations.